2012
DOI: 10.1055/s-0040-1703548
|View full text |Cite
|
Sign up to set email alerts
|

A Histopathological Study of Granulomatous Inflammation

Abstract: Granulomatous inflammation is a distinctive pattern of chronic inflammation that is encountered in a limited number of infectious and non-infectious conditions. Recognisation of granulomatous pattern and finding the etiology in a biopsy specimen is very important for specific treatment and outcome of the disease. We aimed at finding the etiology of all granulomatous lesions on tissue biopsy sent for histopathogical examination. A study was done at K S Hegde Medical Academy of Nitte University, Mangalore from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
12
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 2 publications
8
12
2
Order By: Relevance
“…Similar to this study, epithelioid type granuloma was most common type in other studies. 6,7 However, in contrast to this study, the second most common is either foreign body type or histiocytic type in these studies.…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…Similar to this study, epithelioid type granuloma was most common type in other studies. 6,7 However, in contrast to this study, the second most common is either foreign body type or histiocytic type in these studies.…”
Section: Discussioncontrasting
confidence: 73%
“…However, the second most common cause is fungal in this study, whereas it is leprosy in study of Pawale JS et al 7 and Permi HS et al 6 . Rare causes of granulomatous lesion in this study were chalazion, BCG-instillation, tumor-associated, leishmaniasis, Crohn's Adhikari RC et al ZN stain demonstrated acid fast bacilli only in 11.11% cases in this study, whereas it was 20.74% in a study of Permi HS et al, 22.62% in a study of Pawale JS et al and 71% in a study of Krishnaswamy H et al [6][7][8] The low sensitivity of ZN stain may be due to technical reason. The most common fungal infection is aspergillosis, which is comparable to other studies.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations